Extracellular salt bridge networks around S4 implicated in HCN channel gating and heart disease - Kaei Ryu; Go Kasuya; Koichi Nakajo (Proceedings of the National Academy of Sciences, 2025)
The hyperpolarization-activated cyclic nucleotide-gated (HCN) channel is a voltage-gated cation channel that plays a crucial role in regulating cellular excitability, especially in cardiac pacemaker cells and neurons. Its dysregulation is linked to heart diseases such as bradycardia and neurological disorders such as epilepsy, Parkinson’s disease, and neuropathic pain. Structural and functional studies have revealed that the S4 voltage sensor of the HCN channel moves downward during hyperpolarization. Recent structural studies of HCN channels have shown that the extracellular portion of the S4 segment is approximately three helical turns longer than that of voltage-gated K + (Kv) channels. However, whether this extended extracellular part of S4 plays a functional role in gating is still unknown. In this study, utilizing the available HCN4 channel structures, we examined the formation of salt bridges in the extracellular part of S4 with the S5 segment and the S1-S2 linker. Results from charge-swapped mutants and double cysteine mutants suggested that sequential, stepwise salt bridge formation involving the extracellular positively charged amino acids of S4 plays a role in the voltage-dependent gating of HCN channels. Furthermore, we applied voltage clamp fluorometry to confirm that the extracellular salt bridge network affects the S4 movement. This extracellular S4 portion includes disease-related arginine residues, R375 and R378. Our results suggest that disruption of salt bridge formation may perturb the smooth transition of S4 movement and cause HCN channel dysfunction.